(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This article constitutes a philosophical attempt to initiate an interdisciplinary conversation between philosophy and architecture by taking Roma Toloh of the Bajo-Wuring tribe as its central subject of inquiry. Roma Toloh embodies the local ecological wisdom of the Bajo-Wuring people in sustaining and nurturing their relationship with the sea. The study aims to identify the ecological values embodied in the architectural form of Roma Toloh and to explore its impacts on the marine ecosystem. Employing a qualitative research methodology, the study incorporated field observation and in-depth interviews. Informants were selected using purposive and snowball sampling techniques. The research findings indicate that the Bajo people residing in Wuring, Sikka Regency, Flores, possesses a conscious awareness to nurture the marine ecosystem, with the Roma Toloh serving as a potent symbol of their unity with the sea. However, this consciousness is not corresponding proportionally with the current environmental conditions surrounding their settlements. The increasing scarcity of traditional, natural building materials, coupled with the modernization of construction materials are exerting negative impacts on the Roma Toloh, the ecological wisdom it embodies, and the surrounding environment. The shift from traditional to modern building materials has contributed to the degradation of the residential environment and the erosion of the ecological values inherent in the Roma Toloh. The quality of the marine ecosystem has deteriorated as a result of the shifting. Collaborative efforts between local government, the Wuring community, and neighboring societal communities are thus imperative to ensure the preservation of the Bajo-Wuring cultural identity and the Wuring marine ecosystem.